Long-term effect of bariatric surgery on body composition in patients with morbid obesity: A systematic review and meta-analysis. Issue 4 (April 2021) - Haghighat, Neda; Kazemi, Asma; Asbaghi, Omid; Jafarian, Fateme; Moeinvaziri, Nader; Hosseini, Babak; Amini, Masoud
Summary: We performed a meta-analysis to provide quantitative estimates of fat mass (FM) and fat-free mass (FFM) changes in patients following bariatric surgery over 1 year. A systematic search of PubMed, SCOPUS and Web of Science databases was conducted; the pooled weighted mean difference (WMD) and 95% confidence intervals (CI) were calculated using a random-effects model. Thirty-four studies including Roux en-Y gastric bypass (RYGB), sleeve gastrectomy (SG) biliopancreatic diversion (BPD) and gastric banding (GB) were analyzed. RYGB decreased in body FM (−28.99 kg [31.21,  −26.77]) or FM% (−12.73% [−15.14,  −10.32]) or FFM (−9.97 kg [−10.93,  −9.03]), which were greater than SG and GB. Moreover, the FFM% in RYGB group (11.72% [7.33, 16.11]) was more than SG (5.7% [4.44, 6.95]) and GB (8.1% [6.15, 10.05]) groups. Bariatric surgeries, especially RYGB, might be effective for a decrease in FM and maintenance of FFM in patients with morbid obesity in over 1 year.